Jual Beli Tanah dan Bangunan Atas Objek Jaminan Utang - Meyske Tanamal; Teng Berlianty; Theresia Louize Pesulima (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The transfer of land rights is the transfer of land rights from one party to another, either because of an intentional or unintentional legal act.Purposes of the Research: To study and analyze the process of transferring the sale and purchase of land and buildings that have been used as objects of debt guarantees and to examine and analyze the validity of buying and selling land and buildings that have been used as objects of debt guarantees.Methods of the Research: This research is a normative legal research Results of the Research: The results of this study The validity of the sale and purchase of land and buildings that have been used as objects of debt guarantee, i.e. if the sale and purchase is carried out, has fulfilled the legal requirements of the agreement according to Article 1320 of the Civil Code, and the process of transferring the sale and purchase of land and buildings that are used as objects of debt guarantees is carried out in several stages, namely: the certificate of the object of sale and purchase must be redeemed first by first settling/paying off the debt, and after being paid off, the land certificate is confiscated/abolished collateral rights at the Land Office. The next stage is the preparation of the sale and purchase and the stage of making the sale and purchase deed before the Land Deed Maker Official, including the payment of the sale-purchase tax. Then the next stage is the registration of the transfer of rights or registration of the sale and purchase deed to the Land Office.